2020
DOI: 10.1080/17437199.2019.1705873
|View full text |Cite
|
Sign up to set email alerts
|

Do automated digital health behaviour change interventions have a positive effect on self-efficacy? A systematic review and meta-analysis

Abstract: Self-efficacy is an important determinant of health behaviour. Digital interventions are a potentially acceptable and cost-effective way of delivering programmes of health behaviour change at scale. Whether behaviour change interventions work to increase self-efficacy in this context is unknown. This systematic review and meta-analysis sought to identify whether automated digital interventions are associated with positive changes in self-efficacy amongst non-clinical populations for five major health behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 61 publications
(12 reference statements)
2
23
0
1
Order By: Relevance
“…This is consistent with previous qualitative research which emphasised the importance of motivational factors to personalised nutrition (Stewart- Knox et al, 2013;Rankin et al, 2016) and survey research indicating associations between self-efficacy and attitudes and intention to adopt personalised nutrition (Poínhos et al, 2014). This finding is also consistent with research linking self-efficacy to healthy eating (de Borba et al, 2021;Newby et al, 2020;Lo et al, 2019;Churchill et al, 2019;Naughton et al, 2015;Ferranti et al, 2014;Williams et al, 2012;Anderson et al, 2000). That NS-E did not differ between the control and intervention group post-intervention implies it did not impact upon response to the trial and is contrary to previous studies that have observed increased intake of vegetables (Bouwman et al, 2020), increased fruit and vegetable intake (Smith et al, 2020) and reduced fast food consumption (Smith et al, 2020) in response to enhanced self-efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with previous qualitative research which emphasised the importance of motivational factors to personalised nutrition (Stewart- Knox et al, 2013;Rankin et al, 2016) and survey research indicating associations between self-efficacy and attitudes and intention to adopt personalised nutrition (Poínhos et al, 2014). This finding is also consistent with research linking self-efficacy to healthy eating (de Borba et al, 2021;Newby et al, 2020;Lo et al, 2019;Churchill et al, 2019;Naughton et al, 2015;Ferranti et al, 2014;Williams et al, 2012;Anderson et al, 2000). That NS-E did not differ between the control and intervention group post-intervention implies it did not impact upon response to the trial and is contrary to previous studies that have observed increased intake of vegetables (Bouwman et al, 2020), increased fruit and vegetable intake (Smith et al, 2020) and reduced fast food consumption (Smith et al, 2020) in response to enhanced self-efficacy.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence from recent RCT (Bouwman et al , 2020) has indicated that higher self-efficacy can improve vegetable intake and adherence to healthy eating plans. Recent research (Bracken and Waite, 2020) and systematic review (Newby et al , 2020) have implied that self-efficacy is associated with response to digitally delivered behaviour change interventions. Together, this suggests that individuals with higher NS-E would be more likely to achieve healthy dietary behaviour changes following personalised nutrition advice.…”
Section: Introductionmentioning
confidence: 99%
“… 103 People with migraine can increase their self-efficacy and get a greater control of their health by using digital tools. 104 Personalized migraine care can be facilitated by digital tools. 105 Headache care providers can obtain a comprehensive objective overview of the patient including real-time monitoring via sensors and diary recording.…”
Section: Discussionmentioning
confidence: 99%
“…Diversos estudios muestran que las percepciones de autoeficacia juegan un papel significativo en la conducta para hacer actividad física, donde aquellas personas con mayores niveles de autoeficacia muestran frecuentemente un mayor compromiso y adherencia a un programa regular de actividad física que aquellas con niveles más bajos de autoeficacia, lo cual es consecutivamente un fuerte predictor del mantenimiento de actividad física durante al menos seis meses siguientes al inicio del programa 25 . Simultáneamente, se ha establecido que los valores de conocimiento y autoeficacia se correlacionaron positivamente con la conducta de hacer actividad física, pero los valores previos de la autoeficacia se correlacionaron negativamente con cambios en la conducta de ejecutar algun tipo de actividad física, es decir, la adopción inicial y participación voluntaria 26 . En este sentido, la mayor evidencia se concentra en la práctica de yoga, donde se ha observado que su realización regular conduce a la experiencia de un cuerpo sano y entrenado, mejoran el compromiso y la autoeficacia 27 .…”
Section: Autoeficacia En El Desempeño De La Actividad Físicaunclassified